2020
DOI: 10.1590/1413-81232020253.19232018
|View full text |Cite
|
Sign up to set email alerts
|

Violência contra idosos e qualidade de vida relacionada à saúde: estudo populacional no município de São Paulo, Brasil

Abstract: Resumo Objetivou-se identificar a prevalência da violência doméstica contra idosos não institucionalizados e verificar se esta é um fator independente associado aos Componentes Físico (CF) e Mental (CM) da Qualidade de Vida Relacionada à Saúde (QVRS) desses idosos. É um estudo epidemiológico transversal e de base populacional integrante do Estudo SABE (Saúde, Bem-Estar e Envelhecimento). A amostra foi de 1.126 idosos que responderam ao Short-Form 12 Health Related Survey (SF-12), instrumento genérico que avali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
(37 reference statements)
1
3
0
8
Order By: Relevance
“…Regarding the sociodemographic profile of the old people abused, the main results found showed the following prevalence: age group between 60 and 69 years old, women, widows, with a low level of education, and white race/color, which is consistent with other similar studies carried out [9][10][11] such as the one developed in three Brazilian municipalities (Ribeirão Preto, SP, Teresina, PI, and João Pessoa, PB) aiming to identify the sociodemographic characteristics of victims and aggressors, types of violence, and places of occurrence by the analysis of police reports. The researchers found the prevalence of cases in the age group of 60 to 69 years old, female, married, and with low education 9 , differing from the present study about marital status, as the prevalence was of widowed women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the sociodemographic profile of the old people abused, the main results found showed the following prevalence: age group between 60 and 69 years old, women, widows, with a low level of education, and white race/color, which is consistent with other similar studies carried out [9][10][11] such as the one developed in three Brazilian municipalities (Ribeirão Preto, SP, Teresina, PI, and João Pessoa, PB) aiming to identify the sociodemographic characteristics of victims and aggressors, types of violence, and places of occurrence by the analysis of police reports. The researchers found the prevalence of cases in the age group of 60 to 69 years old, female, married, and with low education 9 , differing from the present study about marital status, as the prevalence was of widowed women.…”
Section: Discussionsupporting
confidence: 89%
“…An investigation carried out in the city of São Paulo 11 , an integral part of the SABE study (Health, Well-being, and Aging) with 1,126 old people, found a prevalence of (10%) of violence against this age group. Regarding the sociodemographic characteristics, (59.8%) were female and (59.1%) of white race/color; the findings were similar to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, elderly women have become more vulnerable, given that culturally they are longer at home with a more restricted social circle and are frequently exposed to financial and emotional submission by family members. This subordination favors stressful situations and depressive symptoms, factors which influence the increase of violence (19) .…”
Section: Resultsmentioning
confidence: 99%
“…A variável sexo apresenta uma discrepância entre as literaturas que investigaram a mesma temática. Corroborando os dados expostos, tem-se o sexo feminino como principal alvo do risco e da violência, predominando-se como um acontecimento social presente em todas as etapas da vida da mulher 4,5,14,15 . No entanto, em outros estudos analisados, o maior risco ou até mesmo os casos de violência foram prevalentes no sexo masculino 6,8 .…”
Section: Discussionunclassified